Sudden cardiac death in childhood RASopathy-associated hypertrophic cardiomyopathy: Validation of the HCM risk-kids model and predictors of events - Boleti, Olga D.; Roussos, Sotirios; Norrish, Gabrielle; Field, Ella; Oates, Stephanie; Tollit, Jennifer; Nepali, Gauri; Bhole, Vinay; Uzun, Orhan; Daubeney, Piers E.F.; Stuart, Graham A.; Fernandes, Precylia; et al. (International journal of cardiology, 2023)
RASopathies account for nearly 20% of cases of childhood hypertrophic cardiomyopathy (HCM). Sudden cardiac death (SCD) occurs in patients with RASopathy-associated HCM, but the risk factors for SCD have not been systematically evaluated. To validate the HCM Risk-Kids SCD risk prediction model in children with RASopathy-associated HCM and investigate potential specific SCD predictors in this population. Validation of HCM Risk-Kids was performed in a retrospective cohort of 169 patients with a RASopathy-associated HCM from 15 international paediatric cardiology centres. Multiple imputation by chained equations was used for missing values related to the HCM Risk-Kids parameters. Eleven patients (6.5%) experienced a SCD or equivalent event at a median age of 12.5 months (IQR 7.7–28.64). The calculated SCD/equivalent event incidence was 0.78 (95% CI 0.43–1.41) per 100 patient years. Six patients (54.54%) with an event were in the low-risk category according to the HCM Risk-Kids model. Harrell's C index was 0.60, with a sensitivity of 9.09%, specificity of 63.92%, positive predictive value of 1.72%, and negative predictive value of 91%; with a poor distinction between the different risk groups. Unexplained syncope (HR 42.17, 95% CI 10.49–169.56, p < 0.001) and non-sustained ventricular tachycardia (HR 5.48, 95% CI 1.58–19.03, p < 0.007) were predictors of SCD on univariate analysis. Unexplained syncope and the presence of NSVT emerge as predictors for SCD in children with RASopathy-associated HCM. The HCM Risk-Kids model may not be appropriate to use in this population, but larger multicentre collaborative studies are required to investigate this further. [Display omitted] •Children with RASopathy associated hypertrophic cardiomyopathy (HCM) have a high risk for sudden cardiac death (SCD)•The HCM Risk-Kids risk prediction model used for children with non-syndromic HCM appears unsuitable for use in this cohort•Non-sustained ventricular tachycardia and unexplained syncope emerge as predictors of SCD•Larger collaborations are needed to validate these results and identify specific risk factors for SCD in this population